The Ability to Utilize Cohesive Devices in Report Texts Written by English Department Students - Ni Kadek Chandra Pithaloka; I Gusti Agung Sri Rwa Jayantini (Indonesian Journal of EFL and Linguistics, 2023)
This qualitative research investigates the utilization of cohesive devices in report writing among English Department students. The study delves into the application of grammatical and lexical cohesive devices in the students' report writing that is connected to the students’ ability in promoting the cultural values they have to report. The research employed a comprehensive approach, including the observation on the students’ field study and interview, as well as content analysis to gain deeper contextual insights into language usage and the contribution of authentic activities prior to report writing on environmental and cultural issues. The findings demonstrate the most frequently used devices are "Reference" and "Conjunction" as primary grammatical cohesive devices, while "Ellipsis" and "Substitution" were underutilized. Of all lexical cohesive devices, "Repetition" occurred dominantly, with "Antonyms," "Synonyms," "Hyponyms," and "Meronyms" were less frequently used. In line with the use of cohesive devices in report writing, the study also emphasized how cohesive devices facilitate English department students in conveying cultural values in their report texts through the integration of field study and authentic experiences. By incorporating real-world applications and deeper learning experiences outside the classroom, aligned with the principles of Independent Learning, Independent Campus ‘Merdeka Belajar Kampus Merdeka’ (MBKM) in Indonesia, academic institutions can foster students' language development and competence in report writing.